2009
DOI: 10.1038/ijo.2009.126
|View full text |Cite
|
Sign up to set email alerts
|

Parent-of-origin specific linkage and association of the IGF2 gene region with birth weight and adult metabolic risk factors

Abstract: Objective: The maternally imprinted insulin-like growth factor 2 (IGF2) gene is an important fetal growth factor and is also suggested to have postnatal metabolic effects. In this study, we examined whether common polymorphisms in IGF2 (6815_6819delAGGGC, 1156T4C and 820G4A (ApaI)) and a microsatellite marker in the close vicinity of IGF2 were linked to or associated with birth weight and adult metabolic risk factors. Design and participants: Polymorphisms were genotyped in 199 monozygotic complete twin pairs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Indeed, using data from the Hyperglycemia and Adverse Pregnancy Outcome Study (27), our largest effect size would have given an odds ratio of only 1.11 for a birth weight above the 90th percentile. The lack of association with birth weight is in general agreement with other studies that have sought but not found association between fetal IGF2 SNP variants and birth weight (2830), although associations have been found in some populations (3133). Cord blood IGF-II protein concentrations are associated with birth weight (12,13), but its genetic regulation is not solely due to polymorphic IGF2 variation because other genes in 11p15.5, including the insulin gene variable number of tandem repeats (34), and H19 (13) can influence it.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, using data from the Hyperglycemia and Adverse Pregnancy Outcome Study (27), our largest effect size would have given an odds ratio of only 1.11 for a birth weight above the 90th percentile. The lack of association with birth weight is in general agreement with other studies that have sought but not found association between fetal IGF2 SNP variants and birth weight (2830), although associations have been found in some populations (3133). Cord blood IGF-II protein concentrations are associated with birth weight (12,13), but its genetic regulation is not solely due to polymorphic IGF2 variation because other genes in 11p15.5, including the insulin gene variable number of tandem repeats (34), and H19 (13) can influence it.…”
Section: Discussionsupporting
confidence: 91%
“…insulin like growth factor 1 (IGF1) and IGF2) may program adipose tissue of offspring for obesity. IGF2, one of the best characterized epigenetically imprinted genes, is associated with greater body weight (Gaunt et al, 2001; Souren et al, 2009) and obesity (Faienza et al, 2010; Perkins et al, 2012; Roth et al, 2002). IGF2 DNA methylation and IGF2 gene expression increase with increased subcutaneous fat mass in human (Huang et al, 2012).…”
Section: Factors Influencing Adipogenesis: Current Status Of Knowlmentioning
confidence: 99%
“…S5). 15,[31][32][33] Several SNPs proximal to the IGF2 gene were associated with DNA methylation at IGF2 DMR0, both when assessed individually ( Fig. S6) and as part of multi-marker haplotypes (Table S3).…”
mentioning
confidence: 99%
“…Eleven SNPs spanning the IGF2/H19 region were selected for genotype analysis based on previously published associations with physiological-and growth-related phenotypes. 15,31,63,64 The location of these SNPs is shown in Figure 1. Eight of the selected SNPs (rs3842773, rs3741211, rs3213221, rs3213223, rs680, rs3168310, rs2839701, rs217727) were genotyped using a multiplex SNaPshot assay (Applied Biosystems, CA) following the manufacturer's standard protocol.…”
mentioning
confidence: 99%